2009
DOI: 10.1016/j.otohns.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the spinal accessory nerve and its relevance to level IIb lymph nodes

Abstract: Our results may help to minimize the incidence of injuring the SAN in the upper neck during ND. Neck level IIb would contain more LNs if the course of the nerve leans toward the ventral side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 20 publications
2
39
1
2
Order By: Relevance
“…This type of architecture is classified as fenestration, since it features window-like openings. According to this classification, 15 cases of fenestration of the IJV, similar to the present case, have been reported in the English literature [5][6][7]. Interestingly, the SAN passes through the duplicated IJV in almost all cases.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This type of architecture is classified as fenestration, since it features window-like openings. According to this classification, 15 cases of fenestration of the IJV, similar to the present case, have been reported in the English literature [5][6][7]. Interestingly, the SAN passes through the duplicated IJV in almost all cases.…”
Section: Discussionsupporting
confidence: 65%
“…In the most recent prospective study, Lee et al [5] encountered this anomaly in 5 (2.8%) cases during 181 NDs. In our study, the clinical incidence was 4 (2.1%) per 192 unilateral NDs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In all the reported cases, SAN received these contributions deep in the SM [8,9]. For the first time, we are reporting the presence of communicating branch in the posterior triangle.…”
Section: Introductionmentioning
confidence: 74%
“…Most of these contributions come from the C2, both C2 and C3, or C3 spinal nerves [8]. In a study, Lee et al, [9] found the contributions from C2 in 53.1% cases; from C2 and C3 in 38.1% cases and anatomy Section…”
Section: Discussionmentioning
confidence: 96%